O fascículo didático “Conhecendo os solos de Silvânia” como proposta para o ensino e popularização do conteúdo de solo - Carvalho, Isabela Ruconsve (2023)
Soil is crucial for the development and maintenance of all life on earth. It performs essential functions such as carbon sequestration, habitat for organisms, nutrient cycling, climate regulation, water purification and contaminant degradation, it is also the foundation of human infrastructure. Due to its social and environmental relevance, the soil theme is addressed in several areas of knowledge. This theme is especially relevant for understanding the phenomena resulting from the processes of land use and occupation expressed in the landscape. In this context, the school plays a fundamental role in promoting teaching and learning in basic education. It is understood that teaching actions and strategies can be leveraged from the use of didactic materials aimed at popularizing soil in school geography and other disciplines. Thus, this research aimed to analyze the potentiality of the didactic booklet for the mobilization of geographic knowledge about the soil in the teaching of Geography. The specific objectives of the research are: a) reflect on the geographic knowledge that constitutes the soil; b) emphasize the importance of cartographic and pedological knowledge in soil reflection; c) investigate the perception of professors in the evaluation of the didactic booklet; d) expand the didactic material Knowing the Soils of Silvânia (GO) Carvalho et al. (2020) with a focus on connections between soils and the local landscape; e) to contribute to the popularization of soil content in basic education in Silvânia. Based on qualitative research procedures, specifically on the case study, this work has the municipality of Silvânia as a spatial cut. Thus, an analysis of themes related to soil in basic education of the subject of Geography and Science in basic education (especially elementary education II) arranged in the Base Nacional Comum Curricular and in the Curricular Document for Goiás was elaborated. Thematic maps were prepared aiming at the spatialization and physical characterization of the surroundings of the elementary schools in the municipality and the contextualization of the soil and other physical-natural components in the urban and rural landscape of Silvânia. In addition, virtual questionnaires were developed aimed at primary school teachers in Silvânia, aiming to understand the teacher's analysis regarding the didactic booklet Knowing the Soils of Silvânia (GO) Carvalho et al. (2020). Subsequently, a qualitative analysis of the results of the applied virtual polls was carried out, from these surveys the aspects of expansion of the didactic fascicle were listed, as well as the final wording of the expanded edition of the fascicle. Data analysis indicated the need for a systemic approach to the soil, integrated with the physical-natural and socio-spatial aspects of the landscape based on the discussions and approaches to the soil in the various didactic materials in basic education. It is understood that the potential of popularizing soils through the elaboration of didactic material, especially the didactic booklet, will be expanded from the appreciation of the following aspects: a multidisciplinary and interdisciplinary approach to the content of soil addressed in the school curriculum; focus on scalar relationships of soil-related phenomena; focus on the local scale, with an approach to physical and natural aspects, historical, cultural and economic characteristics, and the processes of land use and occupation; appreciation of the principles of geographic reasoning in the analysis of local and global phenomena related to the soil; contextualization of cartographic and pedological knowledge; valuing teacher participation; appreciation of the functions of the didactic text in the process of elaborating the didactic fascicle and the valorization of ludic aspects related to the language and iconography of the didactic fascicle.